PENERAPAN HUKUM KESEHATAN DALAM PROGRAM REHABILITASI NARKOTIKA OLEH INSTITUSI PENERIMA WAJIB LAPOR - Kurniyawan, Indra; Simarmata, Marice (Smart Education, 2025)
Abstract: Abusers and victims of narcotics abuse have the right to receive rehabilitation in accordance with applicable regulations. The application of health law in narcotics rehabilitation programs by Mandatory Reporting Institutions (IPWL) is a very important effort in helping abusers and victims of narcotics abuse. The program focuses not only on physical recovery from medical problems, but also on mental and social recovery. IPWLs appointed by the government must carry out rehabilitation programs for abusers and victims of narcotics abuse in accordance with the standards that have been set. The goal is to restore the condition of abusers and victims of narcotics abuse so that they can integrate themselves back into society and function socially. The standard of rehabilitation services set by the government covers various aspects such as methods, duration, facilities, and costs, this aims to ensure that each individual receives treatment that suits his or her needs. The legal framework underlying this program is Law No. 35 of 2009 concerning Narcotics and Permenkes No. 17 of 2023 concerning Amendments to Permenkes No. 4 of 2020 concerning the Implementation of IPWL. Minister of Health Regulation No. 17 of 2023 which requires medical and social rehabilitation for abusers and victims of narcotics abuse. Through a normative juridical approach, this study highlights various problems regarding the application of health law for abusers and victims of narcotics abuse, therapy for appropriate treatment, and understanding the financing mechanism of accepted therapies. The results of this study are expected to be able to provide an analysis of the effectiveness of the implementation of health law, as well as identify appropriate therapies in the rehabilitation of drug abusers and victims of drug abuse and understand the mechanism in financing it.Keywords: Narcotics Rehabilitation, Drug Abusers/Victims, IPWL Abstrak: Penyalahguna dan korban penyalahgunaan narkotika memiliki hak untuk mendapatkan rehabilitasi yang sesuai dengan ketentuan yang berlaku. Penerapan hukum kesehatan dalam program rehabilitasi narkortika oleh Institusi Penerima Wajib Lapor (IPWL), merupakan upaya yang sangat penting dalam membantu penyalahguna dan korban penyalahgunaan narkotika. Program ini tidak hanya berfokus pada pemulihan fisik akibat masalah medis, tetapi juga pada pemulihan mental dan sosial. IPWL yang ditunjuk oleh pemerintah harus menjalankan program rehabilitasi bagi penyalahguna dan korban penyalahgunaan narkotika sesuai dengan standar yang telah ditetapkan. Tujuannya adalah untuk memulihkan kondisi penyalahguna dan korban penyalahgunaan narkotika sehingga mereka dapat mengintegrasikan diri mereka kembali ke masyarakat dan berfungsi secara sosial. Standar pelayanan rehabilitasi yang ditetapkan oleh pemerintah mencakup berbagai aspek seperti metode, durasi, fasilitas, dan biaya, ini bertujuan memastikan bahwa setiap individu mendapatkan perawatan yang sesuai dengan kebutuhannya. Kerangka hukum yang mendasari program ini adalah Undang-Undang No. 35 Tahun 2009 tentang Narkotika dan Permenkes No.17 Tahun 2023 Tentang Perubahan Atas Permenkes No.4 Tahun 2020 Tentang Penyelenggaraan IPWL. Permenkes No.17 tahun 2023 yang mewajibkan rehabilitasi medis dan sosial bagi penyalahguna dan korban penyalahgunaan narkotika. Melalui pendekatan yuridis normatif, penelitian ini menyoroti berbagai permasalahan mengenai penerapan hukum kesehatan bagi penyalahguna dan korban penyalahgunaan narkotika, terapi untuk penanganan yang tepat, serta memahami mekanisme pembiayaan terapi yang diterima. Hasil penelitian ini diharapkan mampu memberikan analisis efektivitas penerapan hukum kesehatan, serta mengidentifikasi terapi yang tepat dalam rehabilitasi penyalahguna dan korban penyalahgunaan narkotika dan memahami mekanisme dalam pembiayaannya.Kata Kunci: Rehabilitasi Narkotika, Penyalahguna/korban Penyalahgunaan Narkotika, IPWL.